Analysis of X-ray absorption spectra of the K and L 2,3 edges of GaN within the FP-LAPW method - Grad, Gabriela Beatriz; Bonzi, Edgardo Venusto (2023)
Versión enviada del artículo; finalmente publicado en: Grad, G. y Bonzi, E. (2016). Analysis of x-ray absorption spectra of the K and L 2,3 edges of GaN within the FP-LAPW method. Applied Radiation and Isotopes, 110, 244-250. https://doi.org/10.1016/j.apradiso.2016.02.001